HUBUNGAN PENGETAHUAN IBU, POLA MAKAN, DAN HYGIENE SANITASI DENGAN STATUS GIZI BALITA (12-59 BULAN) DI WILAYAH KERJA PUSKESMAS SEMBAYAT KABUPATEN GRESIK - Aprilia Nur Indah Sari; Eka Srirahayu Ariestiningsih; Desty Muzarofatus Sholikhah (Universitas Muhammadiyah Gresik, 2022)
The toddlers’ nutritional status is an health indicator must be considered because it can affect the growth and the development. The aim of this research is to analyze the relationship between mother’s knowledges, eating habits, and hygiene sanitation with the toddlers’ nutritional status (12-59 months) in the work area of Sembayat Public Health Center, Gresik Regency. The research is analitic observational research by using cross sectional design. The respondents in his study are 91respondent. Data collection using questionnaires and toddlers’ weight and height measurements. The data are analyzed by using Lambda test with significance α of < 0.05. The results showed that there is significant relation between mother’s knowledges with the toddlers’ nutritional status BB/U and TB/U. There is no significant relation between eating habits with the toddlers’ nutritional status BB/U and TB/U. There is significant relation between hygiene sanitation with the toddlers’ nutritional status BB/U and TB/U. Almost half of mothers who have good knowledge, have toddlers’ with good nutritional status. Most of toddlers’ families have healthy hygiene sanitation conditions and the toddlers’ have good nutritional status. The toddlers’ eating habits in good category do not mean having good nutritional status, this can be caused by inappropriate mother’s parenting, education efforts related to mother’s parenting are needed to improve nutritional status with parenting practices.